LONG TERM IMPLICATIONS OF CLIMATE CHANGE ON RURAL DEVELOPMENT IN NIGERIA - Dennis Brown, Ewubare; Sammy, Ajisafe Femi (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examined the effects of climate change on rural development in Nigeria. In this paper, rural development was measured by the percentage of the population with access to improved water supply. On the other hand, the measures of climate change employed in this paper are precipitations, variations in temperature and per capita carbon dioxide emissions. Data on the variables were sourced from the World Development Indicators (WDI) and the analytical techniques include descriptive statistics, unit root test, Hansen cointegration test and Fully-Modified Least Squares (FMOLS). The Kwiatkowski Phillips Schmidt and Shin (KPSS) unit test results show that the variables are mixed integrated with combinations of I(0) and I(1). It was observed from the Hansen test for cointegration that the test statistic with probability value (0.192) indicates that the variables are cointegrated. This suggests that the null hypothesis of parameter stability cannot be rejected. It was found from the estimated cointegrating regression model that precipitation and temperature are significant in influencing changes in access to improved water supply in rural Nigeria. Whilst precipitations negatively influenced access to rural water supply, changes in temperature enhanced rural water supply. The negative effects of precipitations on rural water supply could be attributed to the flooding usually associated with precipitations which tend to contaminate the various water sources in the rural areas. On the other hand, per capita carbon dioxide emissions do not significantly affect access to improved water supply in rural area. Given the findings, it was recommended for policy makers to adopt proactive and innovative approaches by synergizing with the relevant stakeholders to significantly address the problem of climate change and improve opportunities for rural development.